Pelatihan Penggunaan Perangkat Lunak Mendeley pada Mahasiswa Tingkat Akhir di Kota Ternate - Irfandi Buamonabot; Ikrima M. Mustafa (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
In the field of education, scientific writing skills are very important for both teachers who want to deliver lectures and students who want to complete their final assignments better. According to the rules that bind a student, conducting research for him is a must. Because of its importance, scientific papers must be made as good as possible, especially in terms of citations and references. In addition, most scientific papers are the result of students' own thoughts in addition to some other people's works that can be consulted further to ensure the quality of the work. Many students still complete their final assignments to date without being able to cite sources properly and correctly; instead, they do it automatically. It is hoped that by participating in this community service program, students in particular will be able to take advantage of training using Mendeley software to further maximize the quality of scientific work when citing all of their own scientific work, including theses. The objectives of this activity are to: (1) increase understanding of how to use Mendeley software, a citation application; (2) increase awareness of the benefits of using Mendeley; and (3) increase insight and talent in using more inventive and informative applications. The results of this activity show how useful this training is for the participants.